Effect of IGF-1 and LEP/ob SNPs on growth parameters of Blanco Orejinegro cattle - Londoño-Gil, Marisol; González-Herrera, Luis; López-Herrera, Albeiro; Rincón Flórez, Juan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The aim of this work was to identify the effect of some SNPs of the IGF-1 and LEP/ob genes, on the growth in animals of the Blanco Orejinegro creole breed (BON) and to evaluate the relationship of age at first calving (AFC) with the curve trajectory. For this, 1217 phenotypic and 439 genomic records of pure BON bovines were used. The Gompertz, Logistic, Von Bertalanffy and Brody models were evaluated. The individual growth curve parameters were estimated and the effect of SNPs of the IGF-1 and LEP/ob genes on the curve parameters was estimated through a linear model. Finally, the association of the curve parameters and the AFC was analyzed trough a linear model. The model that represented the best fit to the growth trajectory was Brody’s. On average, the BON animals presented an adult weight (β0) of 479.9±7.4 kg and a growth rate expressing the daily weight gain as a proportion of the total weight (β2) of 0.002±0.00004. The SNPs rs110654613 (nucleotide change A/G) and rs110959643 (A/G), within the IGF-1 gene, showed a significant effect (p<0.05) on the parameters of the BON cattle growth curve. There were no associations of LEP/ob gene SNPs on the parameters of the BON cattle growth curve. AFC was significantly associated (p<0.05) with the parameters β0 and β2. It is concluded that the use of genomic information for the IGF-1 gene can lead to higher growth rates and earlier.